Correction: Furugaito et al. Antimicrobial Susceptibility to 27 Drugs and the Molecular Mechanisms of Macrolide, Tetracycline, and Quinolone Resistance in Gemella sp. Antibiotics 2023, 12, 1538 - Michiko Furugaito; Yuko Arai; Yutaka Uzawa; Toshinori Kamisako; Kohei Ogura; Shigefumi Okamoto; Ken Kikuchi (MDPI AG, 2024)
The authors wish to make the following corrections to this paper [...]